2017
DOI: 10.1590/1414-462x201700010185
|View full text |Cite
|
Sign up to set email alerts
|

Bioética, imigração e assistência à saúde: tensões e convergências sobre o direito humano à saúde no Brasil na integração regional dos países

Abstract: Resumo Introdução Os fluxos imigratórios são um fenômeno mundial e o Brasil não fica distante desse processo. Embora a migração não repercuta necessariamente como uma ameaça à saúde, ela pode aumentar a vulnerabilidade dos sujeitos, tornando imprescindíveis políticas públicas que garantam o direito à saúde. Este artigo teve como objetivo analisar os aspectos bioéticos relacionados ao cumprimento do direito humano ao acesso aos serviços de saúde pelos imigrantes no Brasil. Método Busca eletrônica na base de dad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
19

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 14 publications
0
21
0
19
Order By: Relevance
“…To such an effect, authors reveal the importance of verbal and non-verbal communication, considering the interpersonal relationship in the care for foreign patients, identified by the need for health professionals to become aware on the meaning of messages sent by the patients, in order to be able to provide care that is more appropriate for their needs. 17,18 In the discursive sequence referring to the cultural barrier the following signifiers emerged: "they have a little fear of talking to a doctor", "they are very inhibited" and "they just seek last case healthcare" that demonstrate the perception of the professionals regarding the behavior of the immigrants in the emergency sector care. Findings from another research also revealed that culturally minority groups interact poorly with the health professionals, being verbally less expressive in comparison with other groups, making this ethnic minority more prone to not having their needs met, as well as having difficulty receiving help to solve their problems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To such an effect, authors reveal the importance of verbal and non-verbal communication, considering the interpersonal relationship in the care for foreign patients, identified by the need for health professionals to become aware on the meaning of messages sent by the patients, in order to be able to provide care that is more appropriate for their needs. 17,18 In the discursive sequence referring to the cultural barrier the following signifiers emerged: "they have a little fear of talking to a doctor", "they are very inhibited" and "they just seek last case healthcare" that demonstrate the perception of the professionals regarding the behavior of the immigrants in the emergency sector care. Findings from another research also revealed that culturally minority groups interact poorly with the health professionals, being verbally less expressive in comparison with other groups, making this ethnic minority more prone to not having their needs met, as well as having difficulty receiving help to solve their problems.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to emphasize that this practice violates the precepts of bioethics and is contrary to the principles settled by the Brazilian health system, which recommends universality, completeness and equity as a way to guarantee access and quality of care provided to the population in the healthcare services in Brazil. 17 Finally, it was possible to verify during the analysis that the meanings produced by the professional discourses, in this discursive block, refer to the presence of limiters that interfere in the healthcare provided to the immigrant population that uses emergency services. To such an effect, it becomes imperative to develop strategies to ease these obstacles by providing comprehensive and holistic healthcare to the immigrant population.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the right to health is present in the Universal Declaration of Human Rights. Health is defined as a condition for a life worthy and indispensable for the enjoyment of other rights, such as equality, education, freedom, integral components for a healthy life (3) .…”
Section: Discussionmentioning
confidence: 99%
“…We have enormous challenges insofar as the Brazilian nursing has an important role in the defense of health with equity and quality of life, assuming a practice based on care (2) . For this reason, the right to health involves the issue of human rights and respect for human dignity (3) .…”
Section: Introductionmentioning
confidence: 99%
“…The socioeconomic, environmental and cultural conditions of the populations in the triple Amazon border are portrayed as precarious due to low income, deforestation, and illegal drug trade existing in the region 8 . In addition to these characteristics, the three countries present contrasting health systems, which complicates the integration-in-health processes of the region 9 , with Brazil being the only one structured under the principle of universality 10 .…”
Section: Introductionmentioning
confidence: 99%